A blend of functional amino acids and grape polyphenols improves the pig capacity to cope with an inflammatory challenge caused by poor hygiene of housing conditions - Fraga, Alícia Zem [UNESP]; Campos, Paulo Henrique Reis Furtado; Hauschild, Luciano [UNESP]; Chalvon-Demersay, Tristan; Beaumont, Martin; Le Floc’h, Nathalie (Springer Nature, 2023)
Background: Dietary supplementation with a blend of functional amino acids (AA) and grape extract polyphenols contributes to preserve intestinal health and growth performance of piglets during the post-weaning period. In the present experiment, we assessed if a supplementation with a mix of AA and grape extract polyphenols during the post-weaning period would persist to improve the pig capacity to cope with a subsequent challenge caused by poor hygiene of housing conditions. Eighty pigs weaned at 28 days of age were fed a standard diet supplemented (AAP) or not (CNT) with 0.2% of a blend of AA (glutamine, arginine, cystine, valine, isoleucine, and leucine) and grape extract polyphenols during the post-weaning period (from week 0 to 6). At week 6, pigs were transferred to a growing unit where 50% of pigs previously fed AAP and CNT diets were housed in good and the other 50% in poor hygiene conditions for 3 weeks (from week 7 to 9; challenge period). All pigs were fed a standard growing diet that was not supplemented with AAP. We measured pig growth performance, plasma indicators of inflammation, digestive integrity, and oxidative status, and scored fecal consistency. Differences were considered significant at P ≤ 0.05. Results: One week post-weaning, pigs fed AAP had lower plasma concentrations of haptoglobin than CNT pigs (P = 0.03). Six weeks post-weaning, plasma concentrations of diamine oxidase (DAO) were lower (P = 0.03) whereas those of vitamin E and A were greater (P ≤ 0.05) in pigs fed AAP compared to CNT pigs. The prevalence of diarrhea was higher in CNT pigs compared to AAP pigs (P < 0.01). During the challenge period, only pigs previously fed CNT diet had lower growth rate in poor than good conditions (P ≤ 0.05). They had also greater plasma concentrations of haptoglobin and oxidative stress index (OSI) and lower plasma concentrations of vitamin E in poor than good hygiene conditions (P ≤ 0.05). Conclusions: Pigs fed AAP diet during post-weaning had less diarrhea and plasma concentrations of a digestive integrity marker, as well as greater plasma concentrations of antioxidant indicators during the post-weaning period. The beneficial effects of AAP supplementation persisted after the post-weaning period as evidenced by the absence of effects of the hygiene challenge on growth and health indicators in pigs previously fed APP. This clearly indicated a greater ability of pigs fed AAP to cope with the poor hygiene conditions.
Keywords: Health; Inflammation; Weaning Transition